Multiple Grammars and the Logic of Learnability in Second Language Acquisition - Roeper, Tom W. (Frontiers in Psychology, 2016)
The goal of this article is to enhance the technical description of multi-lingual speakers in terms of a theory of Multiple Grammars where more than one language utilizes a grammar. The challenge of V2 and its implications for interfaces from the perspective of the L2 learner is the focus. A number of constructions are considered including: Quotation, Topicaliation, Empty subjects and Objects, Expletives, and Subject- auxiliary inversoni.